Molecular cloning, characterization, and expression of two 5-HTRs from the pearl oyster Pinctada fucata martensii - Zhu, Shaojie; He, Yubo; Xu, Qiongyu; Zhang, Jiabin; Yang, Chuangye; Hao, Ruijuan; Li, Junhui; Deng, Yuewen (Frontiers in Marine Science, 2022)
The receptors of serotonin, also known as 5-hydroxytryptamine receptor (5-HTR) can mediate regulatory metamorphosis processes in a variety of mollusks. Studying the mechanisms of metamorphosis of the pearl oyster is significant to elucidate breeding, resource recovery and marine pearl production. In this study, two 5-HTR genes from Pinctada fucata martensii (Pm5-HTR2 and Pm5-HTR4) were cloned. A total of 1623 bp open reading frame was identified in Pm5-HTR2, and a 1185 bp open reading frame was detected in Pm5-HTR4; these open reading frames encoded a 540-residue polypeptide and a 394-residue polypeptide, respectively. We also conducted a domain analysis, which indicated that Pm5-HTR2 and Pm5-HTR4 contained a seven-transmembrane domain and revealed that the receptors had high similarity to Crassostrea gigas 5-HTR2 (54.62%) and 5-HTR4 (66.23%). Sequence analysis demonstrated conserved advanced structure and motifs (the DRY/ERY and NPXXY motifs). The expression pattern analysis revealed high expression levels of Pm5-HTR2 and Pm5-HTR4 during the developmental stages. ISH analysis showed that Pm5-HTR2 was primarily expressed in the FE, B, T, EU, and EL stages and Pm5-HTR4 was mainly expressed in the FE, B, T, D, EU, and EL stages. These results suggest that 5-HTRs may play key roles in P. f. martensii larval metamorphosis.